Biofuels and biotechnology: cassava (manihot esculenta) as research model (2010)
Fuels such as ethanol and biodiesel, obtained from plants and their constituents, have recently received the world’s attention as a true alternative to the global energy supply, mainly because they are cheaper and less contaminant of the environment than the currently used, non-renewable fossil fuels. Due to the pushing biofuel market, the world is currently experiencing an increase of agricultural land devoted to grow crops used to obtain them, like maize and sugar cane, as well as crops that have the potential to become new sources of biofuels. Similarly, this emerging market is boosting the basic research oriented towards obtaining better quality and yield in these crops. Plants that store high quantities of starch, simple sugars or oils, are the target of the biofuel industry, although the newest technologies use also cellulose as raw material to produce fuels. Cassava (Manihot esculenta) is widely grown in the tropics and constitutes a staple food for approximately 10% of the world population. The high starch content of its storage roots, together with the use of conventional and non-conventional breeding turn this crop into an option to obtain better adapted varieties for ethanol production. This reflexion article reviews the current status of biofuels worldwide and at the national level, and discusses the benefits and challenges faced in terms of effect on the environment and the human food chain. Finally, it discusses the potential of cassava as a source of raw material for obtaining biofuels in Colombia.